Akibat Hukum Akta Perpanjangan Sewa Menyewa Yang Memuat Keterangan Palsu (Studi Kasus Putusan Pengadilan Tinggi Denpasar Nomor 34/PDT/2016/PT. DPS) - I Gede Yudi Arsawan; I Gede Yusa (Universitas Widya Gama Malang, 2022)
The agreement as a source of engagement must be made by fulfilling the legal requirements as specified in the Civil Code (KUHPerdata). Because if the agreement does not meet the legal requirements, the engagement that occurs cannot be enforced. The agreement can be null and void if it contains false information. The case of the cancellation of the agreement in the form of an authentic deed due to false information can be found in the Denpasar High Court Decision Number 34/PDT/2016/PT. DPS. In that decision, the Panel of Judges upheld the decision of the first instance court which stated that the original Appellant of the Plaintiff committed an unlawful act because he gave false information so that the Deed of Lease Extension made before a notary became null and void. This research is normative legal research or what is also known as doctrinal legal research. Normative legal research is legal research in the area of legal science itself in a broad sense. It is said to be broad because the science of law is the way it is, entering all aspects of science with the aim of achieving legal goals. The results of this study found that there was negligence by a notary in making the Lease Extension Deed in that case, besides that the result of false information by one of the parties resulted in the Lease Extension Deed being invalid and null and void and the party providing false information must be held responsible and compensate for the losses suffered by the parties concerned.